2022
DOI: 10.14202/vetworld.2022.818-826
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, blood variables, intestinal bacterial content, and morphological measurements of broilers supplemented with Lactobacillus casei-fermented mixture of red rice and aromatic ginger

Abstract: Background and Aim: Natural feed additives are important for broiler sustainability during the post-antibiotic era. This study aimed to evaluate the possible effects of the dietary supplementation of Lactobacillus casei-fermented mixture of red rice and aromatic ginger (FERMIX) on growth, blood profiles, intestinal bacterial content, and morphological measurements of broilers. Materials and Methods: Two hundred broiler chicks were allotted to four groups with five replications, including CONTROL (chicks provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…The same outcome was stated by Elamin et al [55], that were no significant differences in relative and absolute weights of liver, gizzard and intestine of broiler chickens Ross 308 at 6 weeks fed diet containing 0.50 and 0.75% FSP. Also, this observation corroborated the data of Astuti et al [47], who found that 0.25, 0.5 and 1% dietary synbiotic (FERMIX) comprising mixture of red rice and aromatic ginger as prebiotic fermented anaerobically using Lactobacillus casei (probiotic) had no effect on relative weights of heart, pancreas, gizzard, small intestine segments and ceaca although high liver relative weight was achieved by 0.5% FERMIX at 35 days of age in broilers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The same outcome was stated by Elamin et al [55], that were no significant differences in relative and absolute weights of liver, gizzard and intestine of broiler chickens Ross 308 at 6 weeks fed diet containing 0.50 and 0.75% FSP. Also, this observation corroborated the data of Astuti et al [47], who found that 0.25, 0.5 and 1% dietary synbiotic (FERMIX) comprising mixture of red rice and aromatic ginger as prebiotic fermented anaerobically using Lactobacillus casei (probiotic) had no effect on relative weights of heart, pancreas, gizzard, small intestine segments and ceaca although high liver relative weight was achieved by 0.5% FERMIX at 35 days of age in broilers.…”
Section: Discussionsupporting
confidence: 90%
“…High PCV in T3 and T5 could be related to positive infulence of synbiotic composition for stimulation of morphological changes in intestine and increase the absorption capacity and feed efficiency which may in turn induce the increase of red blood cells and PCV for accelerate metabolism under stress [18]. This was confirmed recently by Astuti et al [47], that 0.25 and 0.50% of synbiotic led to enhance synthesis of erythrocytes which reflect on increased hemoglobin and PCV of broilers. Low H/L could be explained by effect of synbiotic to relieve stress and improve resistance against NC and IBD (table 4) and this was similar to what obtained by Abdel Razek and Tony [48].…”
Section: Discussionmentioning
confidence: 60%
“…According to Sarangi et al [ 42 ], adding mannanoligosaccharide and the synbiotics L. bulgaricus, L. plantarum , Streptococcus faecium, Bifidobacterium bifidus, and Saccharomyces cerevisiae to the ration had no impact on the proportion of internal organs and broiler carcasses. In agreement with this, Astuti et al [ 43 ] discovered that feeding broiler chicks a mixture of fermented brown rice and ginger with Lactobacillus casei had no impact on the carcasses or the relative weight of internal organs. This reveals that the synbiotic administration of nutmeg flesh extract and L. plantarum has no detrimental impact on the features of broiler chicken carcasses.…”
Section: Discussionmentioning
confidence: 68%
“…According to our research methodology, and based on similar previous studies [ 10 , 11 ], blood samples were collected from the wing vein of 45 randomly selected broilers of each group at the end of the study. The samples were examined in the laboratory of the Veterinary Clinic of Latvia University of Life Sciences and Technologies, using a Mindray BS200 Clinical Analyzer, with the absorbance photometry method.…”
Section: Methodsmentioning
confidence: 99%
“…In several studies, broilers fed probiotics containing various Lactobacillus spp. presented significantly higher amounts of total protein, including albumin and globulin, as well as significantly lower concentrations of cholesterol, total lipids, and triglycerides in the blood [ 5 , 9 , 10 ]. However, in several studies, when broilers were fed probiotics that included Lactobacillus spp., there were no significant changes in the biochemical blood parameters at the end of the study [ 7 , 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%